2013
DOI: 10.1101/000208
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Population genomics of parallel hybrid zones in the mimetic butterflies,H. melpomeneandH. erato

Abstract: Hybrid zones can be valuable tools for studying evolution and identifying genomic regions responsible for adaptive divergence and underlying phenotypic variation. Hybrid zones between subspecies of Heliconius butterflies can be very narrow and are maintained by strong selection acting on colour pattern. The co-mimetic species H. erato and H. melpomene have parallel hybrid zones where both species undergo a change from one colour pattern form to another. We use restriction associated DNA sequencing to obtain se… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
80
0
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 51 publications
(83 citation statements)
references
References 83 publications
2
80
0
1
Order By: Relevance
“…The combination of large-effect switch loci and small-effect modifiers that we see in the genetic control of Heliconius wing patterning is consistent with this model, but the order in which they occurred is an important aspect of the two-step model, which we currently know little about. It is interesting to note that, in a recent analysis of divergence across hybrid zones between color-pattern races of H. erato and H. melpomene, Nadeau et al (2014) found strong divergence centered on large-effect mimicry loci in both species, but divergence associated with putative modifiers differed between species ( Figure 3C). This result may indicate that large-effect loci are conserved among species but modifiers are not.…”
Section: Molecular Characterization Of Mimicry Locimentioning
confidence: 87%
See 2 more Smart Citations
“…The combination of large-effect switch loci and small-effect modifiers that we see in the genetic control of Heliconius wing patterning is consistent with this model, but the order in which they occurred is an important aspect of the two-step model, which we currently know little about. It is interesting to note that, in a recent analysis of divergence across hybrid zones between color-pattern races of H. erato and H. melpomene, Nadeau et al (2014) found strong divergence centered on large-effect mimicry loci in both species, but divergence associated with putative modifiers differed between species ( Figure 3C). This result may indicate that large-effect loci are conserved among species but modifiers are not.…”
Section: Molecular Characterization Of Mimicry Locimentioning
confidence: 87%
“…This was unexpected because H. melpomene and H. cydno are closely related, partially interfertile species, and their divergent color patterns have been shown to play an important role in mediating reproductive isolation. Giraldo et al (2008), Merot et al (2013), andNadeau et al (2014) have since revealed this to be a general phenomenon: there are populations of the H. cydno relative H. timareta mimicking H. melpomene all along the western side of the Andes mountains. Because hybridization between H. melpomene and the H. cydno/timareta clade is widespread, interspecific gene flow could be the source of their shared warning patterns.…”
Section: Genetic Basis Of Convergencementioning
confidence: 99%
See 1 more Smart Citation
“…This approach can help to reconstruct how genomic differentiation and coupling among barrier effects progress during speciation, assess whether the evolution of coupling and genome congealing (Barton 1983;Flaxman et al 2013 of chromosomal linkage and recombination rate variation in the evolution of coupling (e.g., Gagnaire et al 2013;Nadeau et al 2013;Burri et al 2015;Feulner et al 2015). Comparisons among examples with different overall barriers and different combinations of barrier effects, as well as comparative analyses of replicated and independent events of contact in a given system can also help this reconstruction (e.g., Nadeau et al 2014;Vijay et al 2017). In general, it will be important to identify more systems offering multiple hybrid zones to compare situations where coupling may not be at the same stage across the distribution range (e.g., in common voles [Beysard and Heckel 2014], Hyla frogs [Dufresnes et al 2015], or green toads [Dufresnes et al 2014]).…”
Section: Distinguishing Among Coupling Processesmentioning
confidence: 99%
“…There are a few examples of RADseq genome scans recovering loci previously known to be involved in adaptive divergence (Hohenlohe et al 2010;Nadeau et al 2014). Further, some methylation-sensitive restriction enzymes do preferentially target genic regions of the genome (Pegadaraju et al 2013).…”
Section: If You Radmentioning
confidence: 99%